Correlations Between Prokaryotic Microbes and Stress-Resistant Algae in Different Corals Subjected to Environmental Stress in Hong Kong - Tong, Haoya; Cai, Lin; Zhou, Guowei; Zhang, Weipeng; Huang, Hui; Qian, Pei-Yuan (Frontiers in Microbiology, 2020)
Coral reefs face risks from global climate change and are suffering increasing bleaching events. Previous studies suggest that both algal and microbial partners benefit coral hosts while the nature of interactions between Symbiodiniaceae and microbes and their effect on the coral hosts remains unclear. In the present study, we examined correlations between Symbiodiniaceae and microbes in Montipora spp. and Porites lutea sampled from two contrasting sites of Hong Kong. Results showed that the microbial communities were flexible in both Montipora spp. and P. lutea, and environmental conditions had greater effects on the algal/microbial communities in Montipora spp. Further network analysis showed that a greater number of significant correlations between Symbiodiniaceae and microbes were found in P. lutea than in Montipora spp.; stress-resistant Symbiodiniaceae played more important roles in algal-microbial interactions as well as Symbiodiniaceae community in P. lutea. Since P. lutea survives better in Hong Kong as sea water temperature gradually increases, we conclude that the stress-resistant algal-microbial partnership has the potential to provide a compensation mechanism allowing coral hosts to adapt to higher temperatures, particularly since the microbes correlated with Symbiodiniaceae provide the ecological functions of photosynthesis and nitrogen fixation.